Тритомна історія візантійської економіки - Домановський, А. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
Рец. на кн.: The Economic History of Byzantium. From the Seventh through the Fifteenth Century/ Editor-in-Chief A. E. Laiou. – Washington, D. C.: Dumbarton Oaks Research Library and Collection, 2002. – Vol. 1-3. – 1205 p. (in three volumes as number 39 in the series Dumbarton Oaks Studies)